Doktrin Roh Kudus (Pneumatologi) - Nafaya Yesilia; Liska Meri Monika; Deci Natalia; Sarmauli Sarmauli (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
Doctrine of the Holy Spirit, or Pneumatology, which is an integral part of Christian theology. The Holy Spirit acts as the third person in the Trinity, playing a significant role in the lives of believers. In the biblical context, the Holy Spirit is involved in creation, empowering Jesus, and being sent as a Helper to believers. The Pentecost event marks the outpouring of the Holy Spirit, equipping the church to fulfill God's mission. Furthermore, the Holy Spirit provides gifts to each believer, guides them in decision-making, and shapes Christian character in accordance with Christ's teachings. The intimate relationship between the Holy Spirit and believers includes presence, guidance, conviction, and empowerment for service. By understanding the role and work of the Holy Spirit, Christians are expected to live a life pleasing to God and become witnesses of Christ in the world.